Health care professionals' perspective on children's participation in health care situations: encounters in mutuality and alienation. Issue 1 (1st January 2018) - Harder, Maria; Söderbäck, Maja; Ranheim, Albertine
ABSTRACT: Purpose : Encounters between health care professionals, parents and children in health care services for children are complex as these encounters involve the various perspective and understanding of each person involved. The aim of the study is to describe health care professionals' understanding of significant encounters with children and parents to uncover the meaning of participation. Method : A qualitative descriptive design was applied. The health care professionals' narratives (n = 35) of their significant encounters with children were interpreted from the perspective of participation. A phenomenological-hermeneutical approach was used in the analysis. Results : The findings show children's participation as a dynamic movement in mutuality and alienation which can vary within a situation or between different situations involving the same persons. The movement can occur in mutuality and or in alienation depending on what or towards whom the persons direct themselves. Understanding participation as a movement in health care situations is useful in supporting children's opportunities to participate from their own perspective and deal with health care examinations. Conclusion : The outcome of a situation can never be predicted. Still, professionals can be aware of their actions in encounters with children.